1998
DOI: 10.1007/s001220050762
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci associated with acylsugar accumulation using intraspecific populations of the wild tomato, Lycopersicon pennellii

Abstract: Lycopersicon pennellii LA716, a wild relative of tomato, is resistant to a number of insect pests due to the accumulation of acylsugars exuded from type IV trichomes. These acylsugars are a class of compounds including both acylglucoses and acylsucroses. Intraspecific populations between L. pennellii LA716 and L. pennellii LA1912, the latter an accession that assorts for low-level acylsugar accumulation, were created to study the inheritance of type IV trichome density, acylsugar accumulation levels, percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 13 publications
3
42
0
6
Order By: Relevance
“…Extensive breeding programs that focused primarily on larger fruit yields may have decreased the amount of defensive terpenoids produced in the vegetative part of the plant, perhaps indirectly through the reduction in trichome density in cultivated tomatoes as compared with the density found in wild species (Blauth et al, 1998;Simmons et al, 2003). Until this work, there was scant evidence for the expression of tomato TPS genes in the EST databases.…”
Section: Resultsmentioning
confidence: 99%
“…Extensive breeding programs that focused primarily on larger fruit yields may have decreased the amount of defensive terpenoids produced in the vegetative part of the plant, perhaps indirectly through the reduction in trichome density in cultivated tomatoes as compared with the density found in wild species (Blauth et al, 1998;Simmons et al, 2003). Until this work, there was scant evidence for the expression of tomato TPS genes in the EST databases.…”
Section: Resultsmentioning
confidence: 99%
“…Se por um lado, os desvios da segregação mendeliana não parecem, portanto, ter ocorrido nos estudos de Resende et al (2002b), uma vez que as conclusões foram idênticas às obtidas neste trabalho; por outro lado, os resultados aqui encontrados não necessariamente excluem os de Mutschler et al (1996) e Blauth et al (1998), que encontraram diferentes regiões cromossômicas, que afetam algum aspecto da produção de acilaçúcares; pois sendo os acilaçúcares um grupo bastante variado de ésteres de glicose e de sacarose, cuja porção acil varia de 4 a 12 carbonos (Burke et al, 1987), não seria surpreendente que sua síntese fosse afetada por mais de um gene, embora o efeito métrico no teor total pudesse essencialmente ser o de um loco apenas, que controlasse uma etapa crítica do processo de síntese (por exemplo, a reação de esterificação).…”
Section: Resultsunclassified
“…Mutschler et al (1996) também trabalharam com a geração F 2 , de um cruzamento entre L. esculentum x L. pennellii 'LA-716', e indicaram duas regiões no cromossomo 2, além de uma região em cada um dos cromossomos 3, 4 e 11, que afetavam um ou mais aspectos da produção de acilaçúcares. Blauth et al (1998) demonstraram a associação de dez regiões genômicas associadas à produção de acilaçúcares, em genótipos oriundos do mesmo cruzamento interespecífico. Entre essas regiões, os autores destacam os cromossomos 3, 4 e 10 e ainda relatam que o loco gênico do cromossomo 4 está associado à área foliar apresentada pela planta.…”
Section: Introductionunclassified
“…Furthermore, Samarajeewa et al (2005) found that the plants resistant to infestation with B. tabaci had more trichomes on their leaves and stems than the susceptible plants. Also, diff erent compounds, such as acyl sugars, methyl ketones, terpenes, and alkaloids in tomato leaves, confer resistance to numerous insect pests of tomatoes, including aphids (Macrosiphum euphorbiae and Myzus persicae) and whitefl y (B. argentifolii) (Rodriguez et al 1993;Blauth et al 1998).…”
Section: Infestation Suitability Between Tomato Varieties Under Greenmentioning
confidence: 99%